The Gen Z Stare on Reddit: Youth Nonverbal Communication in the Contemporary Era - Cleone Fiona Calalo; Bella Antoni Javier; Charlize Sofia Las; Shyannah Olegario; Angelo Yzmael Salces; Lailah Gabrienne Sarmiento; Dr. Leslie Anne Liwanag; Lois Mauri Anne Liwanag (Future Science / FSH-PH Publications, 2026)
The “Gen Z Stare” is a blank or expressionless stare given in response to situations where verbal reactions are expected. Based on online Reddit discussions, this study aims to identify (1) its contexts, (2) its motivation, (3) and its place in intergenerational miscommunication. The findings suggest that the stare is a form of nonverbal communication associated with emotional avoidance, digital socialization, and limited social skills. It commonly occurs under social pressure, in customer-service interactions, or when encountering “offensive” or “nonsensical” statements, and is usually caused by emotional fatigue, an anxiety freeze response, or a way of setting boundaries. Older generations frequently misinterpret it because of their difference in terms of communication norms and digital exposure. This study imparts a more critical understanding of the social and psychological factors associated with Gen Z communication practices and could substantiate further inquiry into comparable nonverbal expressions among younger generations.